Effects of Online Ruesi Dadton Exercise on Physical Fitness and Body Composition in Overweight Volunteers - พิสัยพันธุ์ รัชฎาพร; บัวพร รัตนาภรณ์; แผ่นคำ จันทร์ธิมา; สิงห์ทอง ปริยาภัทร (Journal of Health Science of Thailand, 2026)
This objective of this study was to investigate the effects of online Reusi Dat Ton exercise on body composition and physical fitness among individuals with overweight. It was conducted as a pilot study with random allocation. Twenty participants were allocated into two groups (n = 10 per group). The intervention group performed Reusi Dat Ton exercise at home via an online platform using a Reusi Dat Ton exercise video, for 40 minutes per session, three sessions per week, for 4 weeks. The control group continued their usual lifestyle and did not participate in Reusi Dat Ton exercise. Body composition and physical fitness were assessed before and after the intervention period. For physical fitness outcomes, the Reusi Dat Ton group showed significant improvements in left-hand grip strength and the sit-to-stand chair test repetitions after training (p<0.05). In particular, left-hand grip strength in the intervention group was significantly greater than that in the control group (p<0.05). Regarding body composition, fat-free mass (FFM), muscle mass, total body water (TBW), and basal metabolic rate (BMR) increased significantly (p<0.05). In conclusion, four weeks of online Reusi Dat Ton exercise improved left-hand grip strength and sit-to-stand performance; and increased fat-free mass, muscle mass, total body water, and basal metabolic rate in individuals with overweight.